Mangrove-mudflat connectivity shapes benthic communities in a tropical intertidal system. (November 2021) - Meijer, Kasper J.; El-Hacen, El-Hacen M.; Govers, Laura L.; Lavaleye, Marc; Piersma, Theunis; Olff, Han
Highlights: Landscape configuration defines mangrove and mudflat connectivity. Macrobenthic communities are influenced by backyard mangrove forests. Seascape consideration is critical in integrative, cross-habitat conservation. Abstract: Understanding the connectivity among seascape habitats is an important emerging topic in marine ecology and coastal management. Mangroves are known to provide many ecosystem services such as coastal protection and carbon cycling, but their functional relationships with adjacent benthic intertidal communities are less clear. We examined how spatial adjacency to mangroves affects macrobenthic communities of intertidal mudflats in a tropical estuarine ecosystem. In the Bijagós Archipelago, Guinea-Bissau, benthic macrofauna assemblages were compared among sampling locations with different connectivities between intertidal mudflats and mangrove stands. We explored how a single mangrove connectivity index (MCI), combining mangrove tidal basin size and the distance to the mangrove edge, affected macrobenthic composition, and compared this effect to sediment properties. In addition, we used structural equation modelling (SEM) and ordination to determine how different environmental predictors directly and indirectly affected macrobenthic communities. MCI strongly affected macrobenthic composition and species abundance, and SEM revealed that this effect contained both a direct component and an indirect component through mudflat NDVI (normalized difference vegetation index, an indicator for microphytobenthos). Sediment properties (grain size, organic matter) affected macrobenthos independently from MCI, nevertheless sediment properties were also affected by MCI. We show the importance of accounting for the seascape structure of tidal basins when investigating the connectivity between mangroves and macrobenthic communities of intertidal mudflats. As benthic macrofauna is a key food source for endangered fish and waders in these systems, our findings provide strong arguments for the integrative conservation of intertidal mudflats and mangroves at the seascape scale.